Physical vulnerability in elderly: difference for sex - Keylla Talitha Fernandes Barbosa; Maria das Graças Melo Fernandes; Fabiana Maria Rodrigues Lopes de Oliveira; Anna Beatriz Campos Brasileiro Tiburcio; Alany Bezerra da Rocha Alves; Carlos Eduardo Barbosa Ramos (Universidad de Alicante, 2015)
To identify vulnerable seniors and physically demarcate the differences by sex in relation to sociodemographic and clinical variables. A descriptive, cross-sectional study with a quantitative approach. The study population comprised elderly resident enrolled in a health district of Joao Pessoa area - Paraíba. The sample consisted of 138 elderly. Data were collected through structured interview, conducted in the period from January to March 2014. This study highlights the prevalence of 47.1% physical vulnerability among the elderly, these 70.8% were female and presented problems health, mobility and difficulty in performing activities of daily living. The identification of vulnerable elderly individuals is relevant to sucintar reflections on the topic and encourages other researchers, professionals and students to go deeper in the subject, in order to obtain new information and thus enrich the studies on the subject proposal.